GEOTHERMAL SYSTEM MODELING BASED ON THE GRAVITY DATA OF DOLOK MARAWASâS GEOTERMAL FIELD, SIMALUNGUN REGENCY, NORTH SUMATRA - Jeremi Siregar, Aldio
Indonesia is a country with the highest potential for geothermal resources with a total of 40% of the world's geothermal potential. One of the geothermal fields in Indonesia is the Dolok Marawa geothermal field, Simalungun Regency, North Sumatra. This study aims to model the developing geothermal system in the Dolok Marawa geothermal field. The research was conducted with the analysis of gravity method starting from the processing of CBA data and topography which was previously obtained by PSDG in 2006.The results obtained from the processing were a complete Bouguer anomaly map with an anomaly value range of -9 - 11 mGal with a background density of 2.26 gr / cc. Then the anomalies were separated to obtain the residual Bouguer anomaly using the moving average and second order polynomial methods. The residual anomaly shows anomalous results with a value range of -9 - 8 mGal and -9 to 9 mGal, respectively. From the residual map produced by the two methods, the moving average method was chosen because of better geological correlation. The results of the modeling show that there was an intrusion of magma originating from the Bahtopu hill (?? = +0.54 gr / cm3), Bahtopu andesite lava units ( ?? = +0.20 gr / cm3), Bahtopu dacitic lava (?? = +0.17 gr / cm3),Toba pyroclastic flow (?? = -0.03 gr / cm3), Toba pyroclastic fall (?? = -0.15 gr / cm3), travertine (?? = +0.48 gr / cm3) and alluvium deposits (?? = -0.02 gr / cm3) which are quarter-aged. The bedrock in this area is interpreted as a Bahbotala limestone unit with a tertiary age (?? = +0.12 gr / cm3). There is a fault structure pattern in the study area according to the research that allows heat flow to the surface.